Transforming Medical Decision-Making: A Comprehensive Review of AI's Impact on Diagnostics And Treatment - George Edison (CV. Multi Kreasi Media, 2023)
A new era of medical innovations has begun as a result of the quick adoption of artificial intelligence (AI) in healthcare, which is changing many aspects of patient care and medical practice. The various applications of AI in healthcare are examined in this study, with a particular emphasis on the fields of medical imaging, tailored treatment paths, ethical issues, drug development, clinical practice integration, and mental health. Each section explores the potential advantages, difficulties, and probable future directions of AI application, illuminating how AI is changing medical procedures. Artificial intelligence (AI) algorithms are transforming illness detection and patient care outcomes in the field of medical imaging analysis by improving speed and accuracy. Artificial intelligence (AI)-enabled personalized treatment pathways optimize interventions based on unique patient profiles, opening the door for more efficient or patient-centered healthcare. As AI's influence expands, ethical issues including transparency, privacy, and algorithmic bias are crucial, necessitating a careful balance between technological development and ethical behavior. The influence of AI on drug research is broad, enabling faster identification of prospective candidates and therapy personalization. Strong infrastructure, open communication, and alignment of AI with human expertise are required for the integration of AI into clinical practice. While early detection, individualized therapy, and continuous support are made possible by the intersection of AI and mental health, ethical considerations are still crucial to protect patient safety and data privacy. Collaborations between healthcare practitioners, AI developers, researchers, ethicists, and patients become a recurrent theme throughout the study. Interdisciplinary collaboration makes that AI-driven solutions are created, tested, and applied with a focus on ethical, responsible, and patient-centered care. A dedication to achieving a healthy balance between technological advancement and ethical responsibility is necessary to navigate the difficulties of AI as its revolutionary potential continues to emerge in the pursuit of better medical care and wellbeing.